Three taphonomic stories of three new fossil species of Darwin wasps (Hymenoptera, Ichneumonidae) - Alexandra Viertler; Fons Verheyde; Martin Schwarz; Georg Schulz; Seraina Klopfstein; Bastien Mennecart (Scientific Reports, 2024)
Abstract Amber captures a snapshot of life and death from millions of years in the past. Here, the fate of three fossil Darwin wasps in Baltic amber is virtually dissected with the help of micro-CT scanning, to better understand the taphonomic processes that affected their preservation. The states of the fossils range from nearly perfect preservation, including remains of internal organs, to empty casts that were strongly affected by decomposition. We describe the three specimens as new taxa, Osparvis aurorae gen. et sp. nov., Grana harveydenti gen. et sp. nov. and Xorides? romeo sp. nov. Based on the taphonomic and morphological interpretations, we conclude that two specimens were trapped alive, and the third ended up in resin post-mortem. The morphology and classification of the specimens provide clues regarding their ecology, and we discuss their likely hosts and parasitation modes. Taken together, our three wasp fossils showcase how an integrative analysis of amber taphonomy, taxonomic association and morphology can shed light onto past biodiversity and offer valuable insights for interpreting their evolutionary history.